2013
DOI: 10.1155/2013/269724
|View full text |Cite
|
Sign up to set email alerts
|

In VitroEffects of Low-Intensity Pulsed Ultrasound Stimulation on the Osteogenic Differentiation of Human Alveolar Bone-Derived Mesenchymal Stem Cells for Tooth Tissue Engineering

Abstract: Ultrasound stimulation produces significant multifunctional effects that are directly relevant to alveolar bone formation, which is necessary for periodontal healing and regeneration. We focused to find out effects of specific duty cycles and the percentage of time that ultrasound is being generated over one on/off pulse period, under ultrasound stimulation. Low-intensity pulsed ultrasound ((LIPUS) 1 MHz) with duty cycles of 20% and 50% was used in this study, and human alveolar bone-derived mesenchymal stem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 41 publications
3
33
0
Order By: Relevance
“…Claims have been made about pain relief with the aid of ultrasound equipment, but these are not supported by scientific evidence [6,7]. Several studies have suggested increased tissue repair owing to ultrasound exposure [8,9], which has led to the increased use of ultrasound equipment when treating bone fracture [10]. However, the acoustic setups of these [8][9][10] and other [11][12][13][14] tissue-repair studies have been such that thermal effects could not be ruled out.…”
Section: Introductionmentioning
confidence: 99%
“…Claims have been made about pain relief with the aid of ultrasound equipment, but these are not supported by scientific evidence [6,7]. Several studies have suggested increased tissue repair owing to ultrasound exposure [8,9], which has led to the increased use of ultrasound equipment when treating bone fracture [10]. However, the acoustic setups of these [8][9][10] and other [11][12][13][14] tissue-repair studies have been such that thermal effects could not be ruled out.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have proposed that ultrasound treatment enhances the repair of fractured bone (Hasuike et al 2011;Ishihara et al 2014;Lim et al 2013;Yang and Park 2001); however, the energy from non-targeted exposure to ultrasound can diffuse, resulting in a decrease in positive effects. Therefore, in this study we investigated focused ultrasound (FUS), which can deliver highly focused acoustic energy to specific areas of biological tissues as small as a few millimeters in diameter .…”
Section: Introductionmentioning
confidence: 99%
“…Reports have shown that acoustic loading increases expression of SDF-1 and CXCR4, thereby resulting in mesenchymal stem cells migration to the fracture site. In spite of that, more investigation is needed to clarify the exact cascade of reactions triggered by SFD-1/ CXCR4 [56,[87][88][89].…”
Section: Signalling For Migrationmentioning
confidence: 99%